SET and MYND domain-containing protein 2 (SMYD2): a prognostic biomarker associated with immune infiltrates in cervical squamous cell carcinoma and endocervical adenocarcinoma - An, Zhanglu; Cai, Danyang; Lin, Xiongzhi; Xu, Shuaijun; Bin, Jin; Jin, Xiaojun (Archives of Biological Sciences, 2022)
Paper description: Cervical cancers are diagnosed at an advanced stage. There is an urgent need to identify a biomarker to predict prognosis. We examined the prognostic value and expression level of SMYD2 in cervical cancer and explored the exact mechanism by SMYD2 knockdown in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC) cells. SMYD2 promotes cell growth and migration. High SMYD2 expression in the cervical cancer microenvironment is linked to poor prognosis and tumor-infiltrating immune cells. SMYD2 is a potential predictive biomarker that could serve as a promising molecular therapeutic target for cervical cancer. Abstract: The histone lysine methyltransferase SET (Suppressor of variegation, Enhancer of Zeste, Trithorax) and MYND (Myeloid-Nervy-DEAF1) domain-containing protein (SMYD2) plays a role in the tumorigenesis of cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). However, the prognostic significance of SMYD2 in CESC and the link between SMYD2 and tumor-infiltrating immune cells are unknown. The prognostic value of SMYD2 in CESC was obtained from The Cancer Genome Atlas (TCGA). SMYD2 mRNA and protein were both highly expressed in CESC compared with normal tissues. The high expression of SMYD2 was associated with advanced tumor status and poor prognosis in CESC patients. SMYD2 was an independent prognostic factor for overall survival. In vitro experiments with knockdown of SMYD2 suppressed CESC cell migration and invasion. The online tumor immune estimation resource (TIMER) and Kaplan-Meier analysis results revealed that the infiltration of CD4+ T and CD8+ T cells was related to poor prognosis. In TIMER-based multivariate Cox regression analysis, CD8+ T cells and SMYD2 were demonstrated as independent prognostic factors of CESC. In conclusion, our data suggest that high SMYD2 expression is a predictor of poor prognosis in CESC patients; SMYD2 could serve as a prognostic biomarker and molecular therapeutic target for CESC.